A mobile clinic approach to the delivery of community-based mental health services in rural Haiti. - J Reginald Fils-Aimé (PLoS ONE, 2018)
This study evaluates the use of a mental health mobile clinic to overcome two major challenges to the provision of mental healthcare in resource-limited settings: the shortage of trained specialists; and the need to improve access to safe, effective, and culturally sound care in community settings. Employing task-shifting and supervision, mental healthcare was largely delivered by trained, non-specialist health workers instead of specialists. A retrospective chart review of 318 unduplicated patients assessed and treated during the mobile clinic's first two years (January 2012 to November 2013) was conducted to explore outcomes. These data were supplemented by a quality improvement questionnaire, illustrative case reports, and a qualitative interview with the mobile clinic's lead community health worker. The team evaluated an average of 42 patients per clinic session. The most common mental, neurological, or substance abuse (MNS) disorders were depression and epilepsy. Higher follow-up rates were seen among those with diagnoses of bipolar disorder and neurological conditions, while those with depression or anxiety had lower follow-up rates. Persons with mood disorders who were evaluated on at least two separate occasions using a locally developed depression screening tool experienced a significant reduction in depressive symptoms. The mental health mobile clinic successfully treated a wide range of MNS disorders in rural Haiti and provided care to individuals who previously had no consistent access to mental healthcare. Efforts to address these common barriers to the provision of mental healthcare in resource-limited settings should consider supplementing clinic-based with mobile services.